Assessing quality in professional services: a framework for gap analysis. (2016) - Omachonu, Vincent; Haar, Jerry; Berg, Daniel
Many of the gap analysis studies of professional services firms have focused on clients' expectations, perception and satisfaction with service delivery. In this research, we develop a framework for the assessment of quality, incorporating ten distinct quality gaps. These gaps take into consideration all the intervening variables which constitute the determinants of quality from the perspective of the clients, industry, and the professional services provider (PSP) respectively. The gap analysis framework developed is based on two focus group sessions - one involving professional services providers, drawn from accounting, management consulting, healthcare, law, advertising, architecture and marketing, and the other involving clients from the same industries. Employing a focus group methodology, the purpose was to understand the nature of the interaction between PSP organisations and their clients and the implications of the interactions on quality. There are subtle and significant differences in the perception of quality between the clients and the PSP. These differences are reflected in the key determinants of quality between both groups.